A comprehensive immunohistochemistry algorithm for the histological subtyping of small biopsies obtained from non‐small cell lung cancers. Issue 6 (6th October 2014) - Koh, Jaemoon; Go, Heounjeong; Kim, Moon‐Young; Jeon, Yoon Kyung; Chung, Jin‐Haeng; Chung, Doo Hyun
<x xml:space="preserve">Abstract</x> Aims Need for accurate histologic subtyping of non‐small cell lung carcinomas (NSCLCs) is growing. IHC patterns may be ambiguous in some cases, rendering it difficult to determine subtypes. Methods and results Tissue microarrays composed of 184 resected NSCLCs were stained for TTF‐1, Napsin A, CK7, p40, p63, CK5/6, and mucicarmine. TTF‐1 and Napsin A were chosen as the most accurate adenocarcinoma (ADC) marker (ACM), and p40 as squamous cell carcinoma (SCC) marker (SCM). We then prospectively performed IHC using these markers (TTF‐1, Napsin A, and p40) in a cohort of small NSCLC biopsies (n = 186) with ambiguous morphology. Of these biopsies, 82.8% (154/186) were classifiable into either ADC or SCC by applying '3‐marker IHC panel'. Additional CK7, p63, and CK5/6 were applied in 30 biopsies with equivocal IHC patterns, including 18 ACM−/SCM− (double‐negative) and 12 ACM+/SCM+ (double‐positive) cases. Decision tree and support vector machine models revealed that TTF‐1 was a critical single marker for ADC in double‐positive cases (91.7% accuracy), whereas p63 and/or CK5/6 helped to subtype double‐negative cases (72.2% accuracy). Conclusions We propose a novel comprehensive algorithm for subtyping NSCLCs using a 3‐marker IHC panel and additional p63 and CK5/6 that would be useful for subtyping small NSCLC biopsies.